The Impact of Consumer Engagement with Gamified Branded Apps on Gameful Experience in Emerging Markets: An Empirical Study - Abbasi, Amir Zaib; Hollebeek, Linda D.; Hassan, Maria; Ting , Ding Hooi; Salm, Eliis; Dikcius , Vytautas (Organizations and Markets in Emerging Economies, 2024)
Drawing on social exchange theory, this article examines how consumers’ engagement with gamified branded mobile apps impacts different aspects of their gameful experience, which comprises accomplishment, competition, challenge, immersion, guidance, playful experience, and social experience. We test the proposed conceptual model by drawing on data collected from 319 adult gamified app users from the emerging market of Pakistan, which was analyzed by using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that consumers’ engagement with gamified branded mobile apps in the emerging market context impacts each of the studied gameful experience dimensions, raising important theoretical and practical implications, as discussed in the article’s final section.